Numerical Computation of Bounded Solutions for a Semilinear Elliptic Equation on an Infinite Strip (Journal of Computational Mathematics, 1999)
In this paper, we consider the computation of bounded solutions of a semilinear elliptic equation on an infinite strip. The dynamical system approach and reduction on center manifold are used to overcome the difficulties in numerical procedure.